2003
DOI: 10.1021/la0348970
|View full text |Cite
|
Sign up to set email alerts
|

Carbonylation and Decarbonylation of γ-Al2O3-Supported Hexarhodium Clusters:  Characterization by Infrared, 13C NMR, and Extended X-ray Absorption Fine Structure Spectroscopies

Abstract: Rh6(CO)16 adsorbed on γ-Al2O3 that had been calcined at 400°C was decarbonylated in steps by treatment in He at increasing temperatures. The metal frame in the supported clusters remained largely intact during the decarbonylation process as evidenced by extended X-ray absorption fine structure (EXAFS) spectroscopy. The face-bridging CO ligands were removed first when the temperature was raised to 100°C and held for 2 h, as shown by infrared and 13 C NMR data. Treatment in He at 300°C led to complete removal of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…He recently co-chaired a DOE workshop on Basic Research Needs: Catalysis for Energy. Rh 6 (CO) 16 also adsorbs without fragmentation of the metal frame on g-Al 2 O 3 , 31,32 MgO, 13 TiO 2 , 14 and zeolite NaY. 17 The adsorption on MgO calcined at 673 K gave a sample with n CO peaks similar to those of [Rh 6 (CO) 15 (COOMg)] À33 and [Rh 6 (CO) 15 ] 2À Mg 2+ .…”
Section: Bruce C Gatesmentioning
confidence: 96%
See 2 more Smart Citations
“…He recently co-chaired a DOE workshop on Basic Research Needs: Catalysis for Energy. Rh 6 (CO) 16 also adsorbs without fragmentation of the metal frame on g-Al 2 O 3 , 31,32 MgO, 13 TiO 2 , 14 and zeolite NaY. 17 The adsorption on MgO calcined at 673 K gave a sample with n CO peaks similar to those of [Rh 6 (CO) 15 (COOMg)] À33 and [Rh 6 (CO) 15 ] 2À Mg 2+ .…”
Section: Bruce C Gatesmentioning
confidence: 96%
“…Moreover, the O atom of a CO ligand can be differentiated from the other light scatterers because of the multiple scattering that occurs when there is a linear arrangement of three atoms. 99 The multiple scattering has been demonstrated for supported carbonyl clusters of osmium, 24,44,50,87 ruthenium, 8,100 rhenium, 77,101 rhodium, 16,32 iridium, 38,102 and others. For example, the Os-C and Os-O* distances (O* is carbonyl oxygen) in supported clusters approximated as pentaosmium carbonyls were found to be 1.91 and 3.11 A ˚, respectively; 50 for comparison, the respective distances in crystalline [Os 5 (CO) 14 ] 2À are 1.88 and 3.05 A ˚.103 EXAFS spectroscopy is usually not sufficient to identify hydrocarbon ligands on supported metal clusters.…”
Section: Iiib Characterization Of Ligands On Metal Framesmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal carbonyl clusters have been explored as molecular precursors of uniform supported metal clusters, , via cluster decarbonylation with retention of the metal framework. For example, Ir 4 /γ-Al 2 O 3 was synthesized by adsorption of Ir 4 (CO) 12 followed by decarbonylation.…”
Section: Experimental and Computational Approaches In The Investigati...mentioning
confidence: 99%
“…In a recent paper the XAFS spectra of a Rh(0) 6 metal cluster and Rh 6 (CO) 16 on alumina showed that the Rh-Rh distances are 2.68 and 2.75 Å, respectively. 9 The XAFS spectrum of the Rh(0) 6 metal cluster resembles that of the bulk metal except the amplitude is lower. However, the absorption spectrum of the Rh carbonyl complex shows a significant phase shift due to the longer Rh-Rh distance.…”
mentioning
confidence: 97%